'Fair Value' accounting as the normative Fisherian phase of accounting. (2nd September 2018) - Cardao-Pito, Tiago; Silva Ferreira, João
ABSTRACT: 'Fair value' accounting has been described as a new 'actuarial/forward-looking' phase of accounting regulations and standards. In this study, we present the hypothesis that 'fair value' regulations and standards are aligned with Irving Fisher's theoretical writings (written more than a century ago) about economic and accounting value, and market prices. Through content analysis, we reveal a literal correspondence of Fisher's writings to key fair value norms from the International Accounting Standards Board (IASB) and Financial Accounting Standards Board (FASB), such as the usage of alleged forecasts of future cash flows and discount rates in explaining market values and prices. Aligning with shareholders/owners interests, Fisher's theoretical framework can be found in contemporary fair value accounting norms.